How to charge while driving: scheduling point-to-point deliveries of an electric vehicle under overhead wiring - Nils Boysen; Dirk Briskorn; Stefan Schwerdfeger (Journal of Scheduling, 2022)
Electrifying road-based long-haul transportation is an intricate task. Given the current state of battery technology, either the driving ranges of electric commercial vehicles (ECVs) are too short or high-capacity batteries are costly and so heavy that payloads are limited. An old, yet recently revitalized, charging infrastructure currently evaluated on multiple test tracks around the globe alternatively suggests charging of electric trucks while driving. Analogously to trams, trolley buses, or trains, ECVs are powered by an electric motor connected to overhead wires via a movable contact arm and supported by a battery or an extra conventional drive, which steps in on non-electrified road segments. This paper is dedicated to the routing of a single ECV executing full-truckload point-to-point deliveries along a highway main line where charge-while-drive infrastructure is fixedly installed along some but not all parts of the road. We formulate the resulting optimization problem, investigate computational complexity, and provide suitable solution procedures based on decomposition. Once all this is available, we explore the induction effect of charge-while-drive technology, i.e., the amount of charging detours required to gather enough energy for the next job. Our results show that the induction effect can be considerable and may lead to substantial extra traffic compared to conventional charge-while-park technology.
Keywords: 650; Green transportation; Electric vehicles; Charge-while-drive technology; Vehicle scheduling.